(untitled) (Indian Journal of Public Health Research & Development, 2025)
Background: COVID-19, which began in Wuhan in December 2019 and became a global pandemic by March 2020, severely strained healthcare systems. In response, the Indian government deployed medical students as COVID-19 assistants to address the healthcare worker shortage. In Gujarat, 5,500 students from various colleges were trained and assigned to public health facilities during the pandemic’s waves. This study investigates the motivations and fears of these students to guide future public health emergency protocols. Methods: This descriptive cross-sectional study was conducted among 1,660 medical students from five medical colleges of Ahmedabad city who participated in COVID-19 duties. Using a pretested questionnaire, data on students’ fears and motivations were collected. Statistical analyses were performed with IBM-SPSS, employing descriptive statistics and independent t-tests, with significance set at p<0.05. Results: Students have mean age of 20.15 years and nearly equal gender distribution. Half of the students reported fear about performing COVID-19 duties, primarily due to concerns about contracting the virus and transmitting it to family members. Motivations for participating included a strong desire to join the healthcare workforce (mean score 3.88) and view the duty as a valuable learning opportunity (mean score 3.82), reflecting a deep commitment to their professional roles. Conclusions: This study finds that while intrinsic motivations such as professional integration and learning opportunities were strong, fears of personal and familial health risks also influenced participation. Despite these fears, students demonstrated notable commitment, highlighting the need for targeted support to balance psychological concerns with professional development during public health crises.